Notes on Astragalus L. section Malacothrix Bunge (Fabaceae) in Turkey: Evidence from seed morphology - Di̇şli̇, Fatma Taeb; Eki̇ci̇, Murat (Phytotaxa, 2026)
In this study, the seed micromorphology of 16 Astragalus taxa belonging to section Malacothrix from Turkey was examined using both Light Microscopy (LM) and Scanning Electron Microscopy (SEM). The seeds exhibited considerable variation in shape, ranging from suborbicular to triangular-ovoid forms, and displayed diverse rugulate-based surface ornamentation patterns, including rugulate, reticulate-rugulate and related types, following recent standardized terminology. Although seed size and colour showed limited diagnostic value, testa ornamentation patterns, particularly when evaluated together with seed shape, revealed consistent interspecific variation and proved taxonomically informative at the species level. Notable patterns such as star-like rugulate ornamentation observed in A. paragriseus or the distinctive verrucate-rugulate structure in A. macrouroides and A. pseudotauricola highlight the diagnostic potential of seed surface characters. Overall, the micromorphological findings presented here contribute to species delimitation and the evaluation of morphologically ambiguous taxa within Astragalus sect. Malacothrix, and support the use of SEM-based seed characters as complementary taxonomic evidence.